INTREPID: single- versus multiple-inhaler triple therapy for COPD in usual clinical practice. Issue 2 (7th June 2021) - Halpin, David M.G.; Worsley, Sally; Ismaila, Afisi S.; Beeh, Kai-Michael; Midwinter, Dawn; Kocks, Janwillem W.H.; Irving, Elaine; Marin, Jose M.; Martin, Neil; Tabberer, Maggie; Snowise, Neil G.; Compton, Chris
Introduction: Real-world trial data comparing single- with multiple-inhaler triple therapy (MITT) in COPD patients are currently lacking. The effectiveness of once-daily single-inhaler fluticasone furoate (FF)/umeclidinium (UMEC)/vilanterol (VI) and MITT were compared in usual clinical care. Methods: INTREPID was a multicentre, randomised, open-label, phase IV effectiveness study comparing FF/UMEC/VI 100/62.5/25 µg via the ELLIPTA inhaler with a clinician's choice of any approved non-ELLIPTA MITT in usual COPD clinical practice in five European countries. Primary end-point was proportion of COPD Assessment Test (CAT) responders (≥2-unit decrease in CAT score from baseline) at week 24. Secondary end-points in a subpopulation included change from baseline in forced expiratory volume in 1 s (FEV1 ) and percentage of patients making at least one critical error in inhalation technique at week 24. Safety was also assessed. Results: 3092 patients were included (FF/UMEC/VI n=1545; MITT n=1547). The proportion of CAT responders at week 24 was significantly greater with FF/UMEC/VI versus non-ELLIPTA MITT (OR 1.31, 95% CI 1.13–1.51; p<0.001) and mean change from baseline in FEV1 was significantly greater with FF/UMEC/VI (77 mL versus 28 mL; treatment difference 50 mL, 95% CI 26–73 mL; p<0.001). The percentage of patients with at least one critical error in inhalation technique was low in both groups (FF/UMEC/VI 6%; non-ELLIPTA MITT 3%). Safety profiles, including incidence of pneumonia serious adverse events, were similar between treatments. Conclusions: In a usual clinical care setting, treatment with once-daily single-inhaler FF/UMEC/VI resulted in significantly more patients gaining health status improvement and greater lung function improvement versus non-ELLIPTA MITT. Once-daily single-inhaler treatment with FF/UMEC/VI results in greater improvements in health status and lung function compared with non-ELLIPTA multiple-inhaler triple therapy in patients with COPD in a usual clinical practice setting https://bit.ly/2PHXNwU